sqrt(12-6*sqrt(3))+sqrt(4-2*sprt(3)

0 голосов
84 оценили
спросил от (15 баллов) в категории Алгебра

sqrt(12-6*sqrt(3))+sqrt(4-2*sprt(3)


2 Ответы
0 голосов
ответил от БОГ (406 тыс. баллов)
 
Лучший ответ

Решите задачу:

\sqrt{12-6\sqrt{3}}+\sqrt{4-2\sqrt{3}}=\\\\\sqrt{9-6\sqrt{3}+3}+\sqrt{3-2\sqrt{3}+1}=\\\\\sqrt{3^2-2*3*\sqrt{3}+(\sqrt{3})^2}+\sqrt{(\sqrt{3})^2-2*\sqrt{3}*1+1^2}=\\\\\sqrt{(3-\sqrt{3})^2}+\sqrt{(\sqrt{3}-1)^2}=\\\\|3-\sqrt{3}|+|\sqrt{3}-1|=3-\sqrt{3}+\sqrt{3}-1=2

0 голосов
ответил от БОГ (232 тыс. баллов)

4-2sqrt(3)=(sqrt(3)-1)^2

12-6sqrt(3)=(3-sqrt(3))^2

sqrt(3)-1+3-sqrt(3)=2

...